DNA barcode for identification of immature stages of sand flies (Diptera: Psychodidae) collected from natural breeding sites - Vivero, Rafael José; Bejarano, Eduar Elías; Estrada, Luis Gregorio; Flórez, Fernando; Ortega-Gómez, Edgar; Aparicio, Yamileth; Torres-Gutiérrez, Carolina; Uribe-Soto, Sandra; Muskus-López, Carlos (Zootaxa, 2017)
Although phlebotomine sand flies breeding sites have been identified and recorded by several studies, the microhabitats exploited by these insects remain little-known and hard to find. In this context, the difficulty of finding immature stages, and the limited number of taxonomic studies to identify immature stages of phlebotomine sand flies, are considered the major obstacles when attempting a complete inventory of Lutzomyia species. The objective of this study is to validate Cytochrome Oxidase I (Barcode region) as a marker for the identification of immature stages of Lutzomyia species recovered from natural breeding sites in Colombia. Among 142 collected sand flies, 18 immature individuals that did not complete their life cycle were identified to species level through sequencing of the COI gene. Values of K2P genetic distance between 0.002–0.031 allowed the identification of larvae at species level. The bootstrap support values (96%) in the Neighbor-Joining dendrogram were consistent for the majority of the established MOTUS of Lutzomyia atroclavata, Lutzomyia micropyga, Lutzomyia serrana, Lutzomyia cayennensis, Lutzomyia rangeliana, Lutzomyia shannoni and some species of the genus Brumptomyia. The COI gene is validated as a marker for the identification of immature stages of the genus Lutzomyia.